RETRACTED: Intravenous versus perineural dexmedetomidine in prolongation of analgesia with regional anesthesia: a meta-analysis and systematic review - Feng, Yan; Chang, Pan; Chen, Xiao-Bo; Yang, Xiao-Lin; Zhang, Yu-Jun; Zhang, Wen-Sheng (Pain medicine, 2021)
This article has been retracted due to the copyright conflicts existing among the authors. Date: 20.08.22